Comparison of different plant layouts and fuel storage solutions for fuel cells utilization on a small ferry. (14th April 2021) - Dall'Armi, C.; Micheli, D.; Taccani, R.
Abstract: In the path towards the decarbonization of the maritime sector, Low Temperature Polymer Electrolyte Membrane Fuel Cells (LT-PEMFC) fed by hydrogen are gaining attention as they could guarantee zero local emissions propulsion. In this study, a process simulation model is implemented to analyze the influence of peak shaving in a hybrid LT-PEMFC/lithium-ion battery power plant for the propulsion of a small size RoRo car and passenger ferry in different operative conditions. Results show that battery peak shaving could allow a reduction of FC installed power of up to 72%. As for compressed H2 storage, the results show that for sailing time in the range of 5–10 min, Type I cylinders at 250 bar are a viable option. For longer routes, Type III cylinders at 350 bar or Type IV cylinders at 700 bar should be considered in order to avoid excessive reduction in the pay-load. Highlights: Overview of marine fuel cells projects. H2 and PEM fuel cells considered for the propulsion of a small RoRo ferry. Different operative profiles analyzed. Energy efficiency improved by 10% compared to diesel oil. Zero local emissions.